2016
DOI: 10.1007/s12221-016-6609-2
|View full text |Cite
|
Sign up to set email alerts
|

Durable antibacterial cotton modified by silver nanoparticles and chitosan derivative binder

Abstract: This article focuses on the functional finishing of textiles using silver nanoparticles (AgNPs) and chitosan derivative binder, which was synthesized by a modification of chitosan using α-ketoglutaric acid. The binder covalently linked to cotton fabric via esterification of the hydroxyl groups on the cotton surface, and tightly adhered to surface of the AgNPs by coordination bonds. As a result, the coating of AgNPs on the cotton fabric showed excellent antibacterial property and laundering durability. After 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 47 publications
1
17
0
1
Order By: Relevance
“…The new materials showed high stability and antibacterial effectiveness even after intensive laundry regimes are employed in hospitals 2,3 . Recently some inorganic metal oxides [4][5][6][7][8][9][10] and metals nanoparticles coated cotton composites have attracted attention, due to significant antimicrobial activities against pathogenic bacteria [11][12][13][14] . Alternative inorganic nanocomposite materials have gained interest due to their safety and selective toxicity against bacteria 10,[15][16][17][18][19] .…”
mentioning
confidence: 99%
“…The new materials showed high stability and antibacterial effectiveness even after intensive laundry regimes are employed in hospitals 2,3 . Recently some inorganic metal oxides [4][5][6][7][8][9][10] and metals nanoparticles coated cotton composites have attracted attention, due to significant antimicrobial activities against pathogenic bacteria [11][12][13][14] . Alternative inorganic nanocomposite materials have gained interest due to their safety and selective toxicity against bacteria 10,[15][16][17][18][19] .…”
mentioning
confidence: 99%
“…For example, antibacterial textiles were produced by incorporating AgNPs into cotton fabrics. It was found that the AgNP-embedded cotton fabrics could withstand 30–50 sequent laundering cycles without losing their antibacterial effect against S. aureus and E. coli [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…And the scissoring and rocking modes of the methylene group were observed at 1462 and 716 cm −1 , respectively, which indicated that AgSt was composed of a triaxial system with two chains per unit cell 43 . It was revealed that it was mainly composed of trace silver and silver stearate 44–45 . This was because of the chemical reaction between stearic acid and WUV@Ag 2 O and the chemical Equations () and () of the reaction were as follows. 2normalNitalicaOH+2AgNO3=2NaNO3+H2O+Ag2O, 2C17H35italicCOOH+Ag2O=2C17H35italicCOOAg+H2O. …”
Section: Resultsmentioning
confidence: 99%